An inexpensive density functional theory‐based protocol to predict accurate 19F‐NMR chemical shifts. Issue 3 (10th November 2021) - Benassi, Enrico
Abstract: Thanks to its advantages, 19 F‐NMR is an increasingly popular technique for the structural characterization of F‐containing molecules, among which polymers, materials, fluorophores, pharmaceuticals, and so forth. However, the computational calculation of the 19 F‐NMR chemical shifts, both for prediction and interpretation of experimental spectra, remains a challenge. In this work a density functional theory (DFT) based protocol for the calculation of the chemical shifts is established within the framework of the gauge‐independent atomic orbital method, upon verifying the performance of Hartree–Fock and 60 DFT functionals coupled with seven different basis sets. The benchmark is conducted using two sets of molecules, namely one used for testing methods and another used for probing; the former set consists of 134 molecules, the latter 50, yet both of them with F in different chemical environments. Following Bally–Rablen–Tantillo strategy, the scaling parameters and other statistical quantities were computed for each method upon least squares linear regression between experimental and computed chemical shifts. The designed computational workflow is computationally inexpensive and represents a significant improvement with respect to the current state of the art. Abstract : The performance of Hartree–Fock and 60 density functional theory functionals (including both pure and hybrid ones) coupled with seven different basis sets in predicting the 19 F‐NMR chemical shifts was systematically checked using two sets of molecules, where F atoms are surrounded by diversified chemical environments.